From Inculturation Theology to Intercultural Exegesis: History, Relevance and Critique (Hekima Review, 2015)
A good number of literatures on Inculturation theology have been focusing on definitions, descriptions, and importance of inculturation theology in Africa. To some extent, the inculturation theology project has been studied with an apologetic undertone and at times seeking to raise awareness among Africa’s upcoming scholars as an invitation to them to take stock of their cultural heritage in their intellectual quest for truth and meaning about the destiny of mankind. For long, I have been battling to understand what inculturation theology could mean in terms of methodological implementation and content-provision in a scholarly engaged programme. Upon pondering the perspectives that Jean Claude Loba-Mkoke proposes in his article on intercultural exegesis, I set to examine its relevance and significance for the future of the inculturation theology in Africa. rough the lenses of intercultural studies of the Scripture, the present article provides an in-depth appraisal of what endorsing inculturation theology could mean. The reader of this article shall indeed and an urgent call to embrace this on-going project with a renewed vigor and clarity of goals to be achieved for Christ’s fuller incarnation in African cultures.